Implementasi Corporate Social Responsibility (CSR) Di Perusahaan Perkebunan Kelapa Sawit PT. Subur Agro Makmur - Fatimah; Saladin Ghalib (JURNAL BISNIS DAN PEMBANGUNAN, 2024)
Abstract: This study aims to determine the implementation of Corporate Social Responsibility (CSR) policies and programs of oil palm plantation company PT. Subur Agro Makmur, as well as knowing the feedback from the community regarding Corporate Social Responsibility (CSR) policies and programs carried out by PT Subur Agro Makmur. This research is descriptive qualitative research. The method of determining research informants using Cluster sampling and Snowball sampling. Data collection techniques use field studies and literature studies. After the data is collected, it is then analyzed with techniques including data reduction, data presentation, and verification. In this study, researchers made direct visits to PT Subur Agro Makmur and the community. The results of the study found that PT SAM in 2021 had carried out a program of CSR activities covering the fields of community economic empowerment, education, health, environment, and religion with a claim of 100% achievement. The largest funds were channeled to the education sector and the smallest to the religious sector. CSR funds come from company administration, not from company profits. Reality shows that what PT SAM does not achieve a balance between the interests of internal and external stakeholders. CSR is used as a tool to achieve goals that are beneficial to PT SAM's internal stakeholders, but do not create great benefits for external stakeholders. The level of sustainability of the CSR programs implemented is also still relatively low. The response from the people who work for the company regarding CSR carried out by PT SAM is quite good. However, it was found that there was a latent conflict that threatened the sustainability of PT SAM, in which the responses from the community outside the plantation who did not work for PT SAM were mostly still negative about the company's existence and there was a feeling of dissatisfaction with CSR implemented by PT SAM. This can illustrate that the implementation of CSR, which is one of the implementations of GCG principles, cannot be said to be optimal, even though PT SAM claims that their CSR achievement during 2021 is 100%.  Keywords: Corporate Social Responsibility, Sustainability, Community Economic Empowerment, Education, Health, Environment, Religion, GCG